Snowbear's Christmas countdown - Smythe, Theresa (New York : Square Fish/Henry Holt and Co., 2009)
During each day of the month of December, Snowbear prepares for and celebrates the Christmas season.
K-3
Accelerated Reader AR
Keywords: Christmas -- Fiction; December -- Fiction; Bears -- Fiction; Counting -- Fiction